Possibilidades formativas no PIBID-UFMT : investigando práticas transcriadoras na formação do professor de Filosofia - Melo, Domingos Sávio Duarte (2017)
In this research, we investigate the possibilities of teacher‘s formation in the Philosophy's PIBID (Institutional Scholarship Program for Teaching Initiation) at Federal University of Mato Grosso from 2010 to 2016. This Program is an initiative from the Federal Government to improve the Higher Education of Elementary and Middle School teachers. It aims to stimulate teachers education through the integration between theory and practice, as well as between university and public school. The thesis was focused on an investigation of possible actions in the PIBID that encourage teaching practices and, specifically, creative (transcreative) practices that contribute to the education of philosophy teachers. Understanding education and formation as a process of creation, we immerse ourselves in the philosophy of difference that refuses to think from the classical philosophy of representation, which judges and evaluates the reality through identity, dogmatic, and immutable models, and therefore, understands that Thinking is to recognize and represent from an intelligible, perfect model. Breaking up with the classical philosophy of representation, it will stimulate the thought to detach itself from a function of mere recognition and activate it as a creative force. From Deleuze, who conceives Philosophy as a producer of concepts, teaching is thought as becoming a creative process, searching resonances in Haroldo de Campos (2013), who deals with the literary translation‘s theory as a creative process (transcreation), and from Sandra Mara Corazza (2013, 2015), who takes the didactics of translation into transcreation as an act of pedagogical creation. From these references, we think of formation from the perspective of becoming, from the creative intensities that throw the thought into an insurgent adventure of creating new worlds, ways of being and acting. We perceived that practices such as planning meetings, diagnosis of school context, teaching methodology, cultural-philosophicalpedagogical formation, didactic projects, observations and interventions in the classroom, participation and presentation of works in events, and a minor formation are actions of the Philosophy's PIBID that stimulated transcreative practices, overcoming traditional pedagogies, and offering a heterogeneity of knowledge in the curriculum of teacher's formation. Deleuze's notion of Procedure guided us in the document's analysis (annual reports), in PIBID productions, as well as in the bibliographical research that approached the theoretical reference on formation, translation/transcreation, philosophy of difference and PIBID, investigating Program's possibility to contribute to the teacher's formation under the lens of the knowledge‘s creation.